2004
DOI: 10.1021/jp036740m
|View full text |Cite
|
Sign up to set email alerts
|

Branching Fractions for H2O Forming Channels of the Reaction of OH Radicals with Acetaldehyde

Abstract: Branching fractions for two hydrogen abstraction channels of the OH + CH3CHO reaction producing H2O + CH3CO (a) and H2O + CH2CHO (b) were determined using chemical ionization mass spectrometry. Reaction took place in a high-pressure turbulent flow reactor at 200 Torr of carrier gas N2. The branching fraction for the abstraction from the methyl group, (5.1+2.4/- 1.7) %, was determined at room temperature by direct detection of the vinoxy radicals (CH2CHO) using proton-transfer ionization. The total H2O yield of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…The reaction of acetaldehyde + OH reaction is assumed to proceed exclusively by the abstraction of the formyl hydrogen atom to produce acetyl radial CH 3 C(O) on atmospheric photochemical models, resulting in overpredicting concentrations of PAN, compared to field measurements [ Roberts et al , 1995]. The kinetics of the reaction of acetaldehyde with OH radical has been investigated extensively [ Cameron et al , 2002; Tyndall et al , 2002; Sivakumaran and Crowley , 2003; Wang et al , 2003; Vanderberk and Peeters , 2003; Butkovskaya et al , 2004]. The possible formation of acids from the OH addition channel during the reaction of acetaldehyde with OH radical is practically neglected since the energy barrier was ∼7 kcal/mol by quantum mechanical methods, approximately 5 kcal/mol and 10 kcal/mol above the H methyl and H aldehydic abstraction channels, respectively [ Alvarez‐Idaboy et al , 2001; D'Anna et al , 2003].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of acetaldehyde + OH reaction is assumed to proceed exclusively by the abstraction of the formyl hydrogen atom to produce acetyl radial CH 3 C(O) on atmospheric photochemical models, resulting in overpredicting concentrations of PAN, compared to field measurements [ Roberts et al , 1995]. The kinetics of the reaction of acetaldehyde with OH radical has been investigated extensively [ Cameron et al , 2002; Tyndall et al , 2002; Sivakumaran and Crowley , 2003; Wang et al , 2003; Vanderberk and Peeters , 2003; Butkovskaya et al , 2004]. The possible formation of acids from the OH addition channel during the reaction of acetaldehyde with OH radical is practically neglected since the energy barrier was ∼7 kcal/mol by quantum mechanical methods, approximately 5 kcal/mol and 10 kcal/mol above the H methyl and H aldehydic abstraction channels, respectively [ Alvarez‐Idaboy et al , 2001; D'Anna et al , 2003].…”
Section: Resultsmentioning
confidence: 99%
“…The possible formation of acids from the OH addition channel during the reaction of acetaldehyde with OH radical is practically neglected since the energy barrier was ∼7 kcal/mol by quantum mechanical methods, approximately 5 kcal/mol and 10 kcal/mol above the H methyl and H aldehydic abstraction channels, respectively [ Alvarez‐Idaboy et al , 2001; D'Anna et al , 2003]. The branching ratio for the H aldehydic abstraction versus H methyl abstraction has been determined to be >0.9 by chemical ionization mass spectrometry [ Butkovskaya et al , 2004].…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of aldehyde species by OH proceeds by H-atom abstraction from the aldehydic group, leading to the formation of acyl peroxy radicals, RC(O)O 2 . For instance, the oxidation of acetaldehyde will lead to the formation of the acetyl peroxy radical, CH 3 C(O)O 2 , with a yield of approximately 95 % (Cameron et al, 2002;Butkovskaya et al, 2004). The reaction of acyl peroxy radicals with HO 2 is known to efficiently recycle OH in the atmosphere.…”
Section: Oh Reactivity Measurements In the Presence Of Isoprene Mvkmentioning
confidence: 99%
“…Vandenberk and Peeters employed molecular beam/mass spectrometer sampling in a flow reactor to deduce an H 2 O yield of 89 ± 6% with an upper limit of 3% to formic acid production [12]. Most recently, Butkovskaya et al applied chemical ionization/mass spectrometry in a flow reactor to determine an H 2 O yield of about 98 ± 5% and, via direct detection of CH 2 CHO, a contribution of channel (1b) of about 5 ± 2% [13]. Two computational studies by Alvarez-Idaboy et al [14] and D'Anna et al [15] via ab initio calculations showed there is a significant barrier to the initial addition step to form an alkoxy intermediate, so that channels (1c) and (1d) would be negligibly slow.…”
Section: Introductionmentioning
confidence: 99%